Thermal radiation and magnetic field effects on unsteady mixed convection flow and mass transfer over a porous stretching surface with heat generation - Reddy, Gurrampati Venkata Ramana; Reddy, B.A.; Reddy, N. Bhaskar (Zielona Góra: Uniwersytet Zielonogórski)
The effects of thermal radiation and mass transfer on an unsteady hydromagnetic boundary layer mixed convection ?ow along a vertical porous stretching surface with heat generation are studied. The ?uid is assumed to be viscous and incompressible. The governing partial differential equations are transformed into a system of ordinary differential equations using similarity variables. Numerical solutions of these equations are obtained by using the Runge-Kutta fourth order method along with the shooting technique. Velocity, temperature, concentration, the skin-friction coefficient, Nusselt number and Sherwood number for variations in the governing thermo physical parameters are computed, analyzed and discussed.
Keywords: radiation; mass transfer; stretching surface; magnetic field; heat generation; temperature